(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
The purpose of this paper is to show that the Indian voice included in Happy Captivity and Reason for the Prolonged Wars of the Kingdom of Chile is not a recognition of otherness, but a useful discursive instrument for achieving the chronicler’s text objective. To that end, we examine the voluntary and involuntary interferences of the soldier’s voice of Francisco Núñez de Pineda y Bascuñán within the written cultural and linguistic transfer from the Araucanian memory. During his captivity, the chronicler has access to its oral configuration and the way in which it is passed on to the members of the group. He interferes in this process –as an actor, during his experience, and as a memory writer a few decades later– and he always does it from a Creole imaginary that retains the fight motivations of ethnocentric thinking, despite having been shaped in the multicultural Araucanian frontier